Interception Studies in Sal (Shorea robusta) and Khair (Acacia catechu) Plantations-new Forest - Dabral, B. G.; Subba Rao, B. K. (Indian Forester, 1969)
The paper presents results of interception studies conducted in sal and khair plantations raised at this Institute. It is seen that sal conducted 7.2, 54.6 and 88.2 percent of rainfall and khair 4.2, 67.8 and 28.5 percent of rainfall as stemflow, through-fall and interception, respectively Maximum number of trees ranged between 17.8 cm to 30.5 cm diameter class in sal and the stemflow, through-fall and interception ranged between 5-10%, 48-58% and 35-40% of rainfall respectively. In khair masimum number of trees were in 10.2 to 20.8 cm diameter range and the corresponding values of stemflow, through-fall and interception were between 2.5-7.0, 64-67 and 27-82% of rainfall respectively. The results are applicable to a dense canopied stand in which maximum interception may take place.